Impact of individual psychological contract breach on organizational citizenship behavior at individual level: Mediating role of trust in supervisor - Athar Marwat; Dr. Adil Adnan (Journal of Business & Tourism, 2021)
This study investigates the relationship between individual psychological contract breach on organizational citizenship behavior at individual level and to test the mediation effects of trust in supervisor. The study was carried out in software industry of KPK, Pakistan. Data was gathered from 337 operational level executive (i.e. executive, assistant manager, manager) through randomly selected sampling method. Numerous statistical techniques (correlation, regression) had been used to deduct the results. Results indicate that individual psychological contract breach significantly predicts organizational citizenship behavior at individual level and with trust in supervisor and fully mediates the indirect relationship between individual psychological contract breach and organizational citizenship behavior at individual level. This research also provides the empirical evidence regarding significance of individual psychological contract grounded on social exchange and affective events theory in the context of KPK, Pakistan. Lastly, contribution of study, limitations and future directions are also discussed.